CRITICAL REVIEW ON BOMBAX CEIBA, ALOE VERA AND XIMENIA AMERICANA - Mane, Rohit Shankar; Vedamurthy, Ankala Basappa (Universal Journal of Pharmaceutical Research, 2020)
Therapeutic plants are extensively increased in scenery with their efficient therapeutic properties. India has the greater natural ecosystem from past two decades, near has been a marvelous augment in the applications of natural medicines; though there is still a noteworthy deficiency in the research of medicinal plants and it has the great resources of medicinal plants which are noteworthy to human beings in many ways. The medicinal plants such as Bombax ceiba, Aloe vera and Ximenia Americana are well known to cure several diseases therefore used in different Ayurvedic preparation somehow they are lagging behind in the list of medicinal plants for their applications in drug preparations. These plants has great ethnopharmaceutical and pharmacological properties with therapeutic applications therefore present review gives different aspects of Bombax ceiba, Aloe vera and Ximenia americana and may help to create awareness in society. Peer Review History: Received 2 February 2020; Revised 10 March; Accepted 25 April; Available online 15 May 2020 Academic Editor: Dr. Ali Abdullah Al-yahawi , Al-Razi university, Department of Pharmacy, Yemen, alyahawipharm@yahoo.com Reviewer(s) detail: Ahmad Najib , Universitas Muslim Indonesia, Makassar, Indonesia, ahmad.najib@umi.ac.id Dr. Mahmut Yıldıztekin , Muğla Sıtkı Koçman University, Turkey, mahmutyildiztekin@mu.edu.tr